ANALISIS KESESUAIAN PENGEMBANGAN PERIKANAN PANCING (HOOaK AND LINE) DENGAN KARAKTERISTIK LINGKUNGAN DAN SOSIAL DI PERAIRAN TELUK TIWORO, SULAWESI TENGGARA - Mustaruddin, Mustaruddin (Jurnal Teknologi Perikanan dan Kelautan, 2017)
After territorial water of Tiworo Bay is specified as conservation area with SK of Head of Muna Regency No. 157 Year 2004, utilization of fisheries resources by local fishermen have a few trouble. This research aim to analysing of compatibility for hook and line fisheries and analysing of it’s development strategic as utilization alternative in location. Research method about analysis of environmental characteristic, compatibility analysis, and hierarchy analysis. Result of the research show that temperature of surface of territorial water of Tiworo Bay are 26,5oC – 29oC, salinitas are 29‰ - 33‰, Hg metal are 0,00045 – 0,0008 ppm, and current is calm enough. Assess of pH is in optimal range (7,0 – 8,5) to fisheris growth, so that very compatible as fishing ground. NKgab of hook and line with area function, area potency, socialize requirement and punish peripheral are each 3,64, 3,25, 3,24, dan 3,3 at scale 1-4, so that it’s compatibility is very good to developed in territorial water of Tiworo Bay. The development of hook and line fisheries with zonasi as bases (importance ratio = 0,278 for inconsistency 0,04) is representing of priority strategy for sustainable development of hook and line fisheries in territorial water of Tiworo Bay.